NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL PULANG KARYA TERE LIYE - Sari, Dahlia Permata; Thahar, Harris Effendi; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2018)
ABSTRACT This research aims to describe the values of character education in the Pulang novel by Tere Liye. This research type is qualitative research with descriptive method. The approach used in this research is the objective approach.This research data is in the form of words, phrases, sentences, and discourses that display events and figures that indicate the values of character education contained in the novel Pulang by Tere Liye. Data collection techniques of this study, namely reading and understanding, inventorying, interpreting, classifying, and concluding data relating to character education values in Pulang novel by Tere Liye and guided by appreciative reading.Â Kata kunci: nilai pendidikan karakter, novel PulangÂ